METHODOLOGICAL APPROACHES TO UNDERSTANDING THE ESSENCE OF THE CONCEPT OF "EDUCATIONAL TECHNOLOGY" - Osadchenko, I.I. (Pedagogy of Higher and Secondary Education, 2022)
In the article by the analysis of versatile methodological approaches to the investigated phenomen the essence of concepi ”technology of education” as a making part of the didactic system is defined. The bo methodological approaches of the training technology stud are systematic, didactic and technological ones.